2006
DOI: 10.1128/jcm.01067-06
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Supporting Zoonotic Transmission of Cryptosporidium spp. in Wisconsin

Abstract: Cryptosporidium hominis and Cryptosporidium parvum are the primary species of Cryptosporidium that infect humans. C. hominis has an anthroponotic transmission cycle, while C. parvum is zoonotic, infecting cattle and other ruminants, in addition to humans. Most cryptosporidiosis outbreaks in the United States have been caused by C. hominis, and this species is often reported as the primary cause of cryptosporidiosis in this country. However, outbreaks account for only 10% of the overall cryptosporidiosis cases,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(159 citation statements)
references
References 42 publications
5
140
1
6
Order By: Relevance
“…Cases of human infection have been reported in Canada (ONG et al, 2002;WONG;ONG, 2006;TROTZ-WILLIAMS et al, 2006), New Zealand (LEARMONTH et al, 2004, United States (FELTUS et al, 2006;BLACKBURN et al, 2006), United Kingdom (LEONI et al, 2006;CHALMERS et al, 2009), andSlovenia (SOBA et al, 2006), among others. The lack of specificity and habitat probably contribute to the widespread distribution of the parasite; the protozoan is routinely found in clear waters, and several animal species release oocysts into the environment (JIANG et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Cases of human infection have been reported in Canada (ONG et al, 2002;WONG;ONG, 2006;TROTZ-WILLIAMS et al, 2006), New Zealand (LEARMONTH et al, 2004, United States (FELTUS et al, 2006;BLACKBURN et al, 2006), United Kingdom (LEONI et al, 2006;CHALMERS et al, 2009), andSlovenia (SOBA et al, 2006), among others. The lack of specificity and habitat probably contribute to the widespread distribution of the parasite; the protozoan is routinely found in clear waters, and several animal species release oocysts into the environment (JIANG et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is concluded that the animal breeding industry should be the major contamination sources of Cryptosporidium oocysts in the studied region. However, it should be noted that among the five animal originated species/genotypes detected in this study, the Cryptosporidium suis has been reported in patients in Peru and England (Leoni et al 2006) and in HIV-infected patients in China (Wang et al 2010a), and the cervine genotype Cryptosporidium has been reported in patients in Canada (Trotz-Williams et al 2006), the United Kingdom (Ong et al 2002), the United States (Feltus et al 2006), and Slovenia (Soba et al 2006). Besides humans, the cervine genotype has also been found in a wide host range including wildlife, zoo, and farm animals (Karanis et al 2007b) and could possibly emerge as an important human pathogen with increasing contact between humans and animals.…”
Section: Initial Precision and Recovery Of Cryptosporidium Parvum Oocmentioning
confidence: 99%
“…The infection is endemic to the Balkans (1,2). In Bulgaria, most cases are reported from the central and eastern parts of the country (3,4).…”
Section: Crimean-congo Hemorrhagic Fever Southwestern Bulgariamentioning
confidence: 99%